Exploring the Nexus Between Country of Origin and Purchase Intentions towards Korea Cosmetics : Evidence from Myanmar’s Market - Atar Thaung Htet (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
Purpose – As the firms reach on global stage to penetrate and grasp global market, country-of-origin (COO) is popular concept for this era.Thus, this study tries to explore country-of-origin (COO) and examine the effect of COO on purchase intentions of Korea cosmetic in Myanmar.The specific objectives of this study are- to explore the consumers’ perceptions on country-of – origin dimensions in Myanmar cosmetic market, to examine the users’ intentions to purchase on Korea cosmetic in Myanmar and to analyze the effect of country of origin on purchase intention of Korea cosmetics in Myanmar.Methodology/approach – The required 193 respondents were selected by convivence sampling techniques in this study. The descriptive statistics and multiple linear regression analysis used in this study in order to analyze the collected data. Quality & technology excellence, product superiority and trust, product class and knowledge and xocentrism were major dimensions of country of origin in this study. Findings – This study found that all of this country-of-origin dimensions except product class & knowledge have positively significant effect on purchase intentions of Korea cosmetics in Myanmar. Novelty/value – Therefore, this study made some practical recommendation for market practioners in Myanmar how to focus on each dimension of country-of-origin produced the effective marketing strategies and suggested the comprehensive frameworks for other emerging markets in south east Asia regions for academic world